PENGARUH LEBAR SUDU TERHADAP KINERJA TURBIN VORTEKS - Yusuf Randabunga; Adhy Kurniawan; Suryo Darmo (ASEAN Journal of Systems Engineering, 2014)
Vortex turbine is the one of turbines which meets those criteria. This turbine utilizes kinetic energy of vortex water and converts it into a shaft power. The objectives of this research were to obtain the torque that could be generated from the vortex  turbine by varying the width of turbine blades and to know  the output  power also the optimum efficiency obtained from this variation. This research was conducted by  using vortex pool in a laboratory scale with a diameter of 108 cm and 6 turbine blades on permanent rotation at 50 rpm, 60 rpm, and 70 rpm. Turbine blades were made from flat rectangular steel with a length of 40 cm sized 1/6, 2/6, 3/6, 4/6 and 5/6 times to radius of vortex pool.The results of the research showed the torque as 1.40 Nm at rotation is 50 rpm. The maximum power is obtained from blade with width of 3/6 times  radius of the pool, that is  8.60 Watts at head 0.362 m and discharge 11.83  l/s or  0.01183 m3/s at rotaion shaft is 70 rpm. This experiment also generated and turbine efficiency of 16.46% at rotation of shaft is 70 rpm.